(untitled) (Research, Society and Development, 2025)
The objective of this review is to assess the effectiveness of electrocoagulation (EC) as a sustainable alternative for the purification of domestic wastewater effluents, considering its potential for contaminant removal, technical and economic feasibility, and its impact on public health and ecosystem protection. This systematic review evaluates EC as a sustainable option for domestic wastewater treatment, with a focus on pollutant removal. Reactor designs, electrode materials, operational parameters, and economic and technological challenges were analyzed based on existing literature. The results show that EC achieves removal efficiencies above 90% for chemical oxygen demand, turbidity, and organic matter, especially when using aluminum electrodes or aluminum-iron combinations. However, pH, electrical intensity, and reactor design are critical factors influencing performance. Although operational costs are higher than those of conventional methods, EC stands out for its versatility and lower sludge generation. This study concludes that EC has significant potential for domestic wastewater purification, although industrial-scale implementation requires optimization of energy consumption and cost reduction.